2007
DOI: 10.1037/0096-1523.33.5.1127
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual and nonvisual feedback in a vehicle steering task.

Abstract: This article investigates vehicle steering control, focusing on the task of lane changing and the role of different sources of sensory feedback. Participants carried out 2 experiments in a fully instrumented, motion-based simulator. Despite the high level of realism afforded by the simulator, participants were unable to complete a lane change in the absence of visual feedback. When asked to produce the steering movements required to change lanes and turn a corner, participants produced remarkably similar behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 36 publications
6
56
0
1
Order By: Relevance
“…Although the exact contribution of the visual cues to the driver's perception is not clear [2], it is known that in the absence of visual cues, drivers are unable to perform some basic driving tasks [3]. Visual perception of motion is made possible primarily by what is usually referred to as "peripheral vision", which originates from the rod-shaped receptors in the retina [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact contribution of the visual cues to the driver's perception is not clear [2], it is known that in the absence of visual cues, drivers are unable to perform some basic driving tasks [3]. Visual perception of motion is made possible primarily by what is usually referred to as "peripheral vision", which originates from the rod-shaped receptors in the retina [4].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was, therefore, to see whether drivers of agricultural vehicles use visual cues from the environment in performing these tasks and whether a driving simulator for these vehicles should include visual cues. Based on the reviewed literature on automobile driving (for example [3]), our null hypothesis is that drivers do need visual cues from the environment for successfully performing turns and maneuvers. Previous research has shown that when driving in straight lines in the presence of crosswind, automobile drivers do not depend on visual cues to a great extent and, instead, increase their use of motion cues such as yaw motion and lateral acceleration cues [22].…”
Section: Introductionmentioning
confidence: 99%
“…Godthelp (1986) and Wallis et al (2007) have shown that visual occlusion does not affect drivers' ability to produce a cornering manoeuvre.…”
Section: Vehicle Steeringmentioning
confidence: 99%
“…Godthelp (1985) (Wallis, Chatziastros et al 2002, Wallis, Chatziastros et al 2007) -see Figure 3. Without visual feedback, drivers only turn the vehicle towards the destination lane (the first steering phase, see Figure 3) but never return the vehicle to the original heading (the second, return steering phase, see (Wallis, Chatziastros et al 2002).…”
Section: Vehicle Steeringmentioning
confidence: 99%
See 1 more Smart Citation